2019
DOI: 10.1111/liv.14121
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, predictive factors and clinical significance of development of portal vein thrombosis in cirrhosis: A prospective study

Abstract: Background and aims: The role of portal vein thrombosis (PVT) in the natural history of cirrhosis is controversial. There are few prospective studies validating risk factors for development of PVT. We analysed the incidence, factors associated with PVT development and its influence on cirrhosis decompensations and orthotopic liver transplant (OLT)-free survival. Methods: In this prospective observational study between January 2014 and March 2019, 445 consecutive patients with chronic liver disease were screene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 43 publications
0
50
0
6
Order By: Relevance
“…Severity of portal hypertension and liver disease are major predictive factors for PVT in patients with cirrhosis. ( 113‐118 ) Decreased velocity of PV flow at baseline has been recognized as a risk factor for PVT in patients with cirrhosis in several studies, albeit with varied predictive value. ( 117‐120 ) Some studies have identified specific thresholds of portal flow associated with increased risk of PVT, ranging from 10 to 15 cm/s, as determined by Doppler ultrasonography.…”
Section: Pvt Prevalence and Risk Factors: Patients With Cirrhosismentioning
confidence: 99%
See 2 more Smart Citations
“…Severity of portal hypertension and liver disease are major predictive factors for PVT in patients with cirrhosis. ( 113‐118 ) Decreased velocity of PV flow at baseline has been recognized as a risk factor for PVT in patients with cirrhosis in several studies, albeit with varied predictive value. ( 117‐120 ) Some studies have identified specific thresholds of portal flow associated with increased risk of PVT, ranging from 10 to 15 cm/s, as determined by Doppler ultrasonography.…”
Section: Pvt Prevalence and Risk Factors: Patients With Cirrhosismentioning
confidence: 99%
“…Other prospective studies have arrived at similar conclusions. ( 114,137 ) In contrast, a small, prospective, randomized controlled trial of enoxaparin compared to no anticoagulation therapy in prevention of PVT in high‐risk patients with cirrhosis ( 125 ) showed not only efficacy in prevention of PVT in the enoxaparin group, but also a survival and decompensation benefit. Although this study has not been replicated, the implication of prolonging decompensation‐free survival with prevention of PVT implies etiological potential.…”
Section: Influence Of Pvt On Mortality In Patients With Cirrhosismentioning
confidence: 99%
See 1 more Smart Citation
“…50,51 Rather, the presence of thrombocytopenia is strongly associated with the development of portal vein thrombosis. 52 Given the underlying perception that patients with decompensated cirrhosis are coagulopathic, there is often suboptimal use of pharmacologic VTE prophylaxis, likely due to misconceptions about bleeding risk. 53…”
Section: Thromboembolic Riskmentioning
confidence: 99%
“…However, this meta-analysis should be evaluated with caution, as it included studies with heterogeneous populations (partial and branch PVT cases were excluded in one study, and partial and total PVT cases were mixed in another). Moreover, the results of the meta-analysis [8] contradict those of many other (primarily retrospective) studies, which have predominantly reported that PVT had no impact on the mortality of patients on waiting lists for liver transplant (LT) [12][13][14][15][16][17][18].…”
Section: Does Pvt Worsen the Outcome Of Cirrhosis?mentioning
confidence: 70%